Cultures of Digitization: A Historiographic Perspective on Digital Art History - Näslund, Anna; Wasielewski, Amanda (Visual resources, 2020)
Art museums began using computers to help organize, catalogue, and coordinate their collections as early as the 1960s. In more recent times, art historians have consolidated the use of digital tools in the discipline within the emerging field of Digital Art History (DAH). In this historiographic study, we set out to understand DAH through an analysis of existing scholarship in the field. Our method combined both text mining and close reading of three datasets of art history journal articles published in the last decade: DAH (International Journal of Digital Art History, special issues of Visual Resources), Art History, and Art Journal. We studied the topical focus of these journals, looking at which agents, materials, and methods dominate and how they are contextualized. Based on this, we found that the subject matter and topical focus of scholarship in DAH differs significantly from scholarship in Art History or Art Journal. More specifically, the historical concerns of museums with regard to digitization still dominate DAH compared to other scholarship in the field. We argue that there are a number of historical and practical reasons for this, including early adoption of computers within museums, the need for simplicity in digitization projects, and issues of copyright. The persistence of this affiliation, in turn, raises critical questions for the future of the field of art history, including who can access art historical datasets, and how and by whom they are created.